LITERASI KEBANGSAAN DAN MODERASI BERAGAMA DI NEGERI LISABATA, NUNIALI, DAN WAKOLO - Agustinus M. L. Batlajery; Fachrul Pattilouw; Rachel Iwamony; Defi Ninkeula (Jurnal PKM Setiadharma, 2022)
Religious, cultural and ethnic diversity in the face of Indonesian people's life. Behind this diversity, there are positive and negative potentials. The positive potential is that Indonesia has people from various backgrounds, so social interactions occur. The community upholds cooperation, mutual respect, and tolerance. These inclusive values ​​are then practised in social life at all levels, including the people of the Taniwel sub-district, West Seram Regency, Maluku Province. Meanwhile, the negative potential is that the diversity that exists also saves space for societal barriers when easily provoked by irresponsible elements, such as violent conflicts in the name of religion that occurred in several parts of Indonesia and hit the Taniwel sub-district. A conflict then changes the way people view diversity in people's lives. As a result, religious harmony is threatened, disintegrating within the community itself. Therefore, this community service activity was carried out considering the lack of understanding among the community about the importance of national literacy and religious moderation. The attitude of religious moderation through strengthening inclusiveness values ​​needs to be built into the community. This is an acknowledgement of the other party's existence and an attitude of respect for differences. This difference then becomes the reason not to hurt each other, suspect, and judge one another. On the contrary, it strengthens and unites each other.